Enjoying coconut free from insect pest infestation - RAO, NBV Chalapathi; Srinivasan, T; Gurav, S S; Rajamanickam, K; Maheswarappa, H P (Indian Horticulture, 2019)
The Integrated pest management integrates all suitable techniques of pest management knowing the natural regulatory factors of environment and ecological principles, major insect pests of coconut can be effectively managed by adopting IPM packages developed. The integrated packages developed are eco-friendly and validation of these packages on large-scale at farmers’ fields strengthens their belief in IPM. Biological control is very much successful in coconut, especially against black-headed caterpillar and inclusion of pheromone lures as a component of IPM opened new vistas in coleopteran pest management in this crop. The palm health achieved through better nutrient management practices stress the importance of agronomical practices in mite management.